NOVEL KINKAKUJI: ANTARA REALITAS DAN FIKSI - Zaki Ainul Fadli (KIRYOKU, 2018)
(Title: Kinkakuji’s novel: Between Reality and Fiction). This paper aims to reveal the similarities between historical or real facts and fiction in Kinkakuji's novel, especially the similarity of Kinkakuji's burner profile to the main character and the timeline equation. The method used in this article is the sociology of literature method and the literature study method. The results showed that there was an equation between the Kinkakuji burner profile and the main character. In addition, there are similarities in the time between historical facts and the time frame found in Kinkakuji's novel.